2022
DOI: 10.4103/sjg.sjg_576_21
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Association for the Study of Liver diseases and Transplantation position statement on the hepatology workforce in Saudi Arabia

Abstract: The field of hepatology has evolved significantly over the last two decades. Hepatology practice in Saudi Arabia (SA) was dominated by hepatitis B and C viruses but is now being overtaken by patients with non-alcoholic fatty liver disease. These patients require greater medical attention as their care is more complex compared to patients with viral hepatitis. In addition, liver transplantation (LT) has expanded significantly in SA over the last three decades. There is a necessity to increase the hepatology wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…supported this statement in their publication which successfully demonstarted the combined medical and NP model of care for patients undergoing liver transplantation. The study demonstrated patients managed under the combined model of care were more likely to undergo consistent toxicity screening compared to patients who were solely managed by the medical team 39 . This is an important consideration in the HSCT population, where meticulous adherence to screening guidelines is a critical component of care delivery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…supported this statement in their publication which successfully demonstarted the combined medical and NP model of care for patients undergoing liver transplantation. The study demonstrated patients managed under the combined model of care were more likely to undergo consistent toxicity screening compared to patients who were solely managed by the medical team 39 . This is an important consideration in the HSCT population, where meticulous adherence to screening guidelines is a critical component of care delivery.…”
Section: Discussionmentioning
confidence: 97%
“…The study demonstrated patients managed under the combined model of care were more likely to undergo consistent toxicity screening compared to patients who were solely managed by the medical team. 39 This is an important consideration in the HSCT population, where meticulous adherence to screening guidelines is a critical component of care delivery.…”
Section: Support Mentorship and Education Provided To Junior Medical ...mentioning
confidence: 99%
“…Similarly, the cases of advanced liver disease secondary to NAFLD, NASH, and HCC are projected to double by 2030, with an annual incidence of liver-related deaths of 4800 [ 36 ]. NASH is likely to be the leading cause of liver transplantation in the Gulf countries due to a reduced burden of viral hepatitis among the resident nationals, in combination with skyrocketing obesity rates [ 36 , 41 , 42 ].…”
Section: Epidemiology Of Hcc Across the Gulf Regionmentioning
confidence: 99%
“…Tumour ablation is a widely accepted treatment option for patients with early‐stage HCC and is followed extensively in the MENA region (Figure 5). 79,85–87 A large proportion of patients in the MENA region are diagnosed at a stage of HCC where surgical therapies are no longer viable due to the extent of the disease, poor hepatic reserve, or coexistent morbidities. The most widely available ablation techniques are percutaneous ethanol injection, RFA and MWA.…”
Section: Overview Of Current Management Strategies Of Hcc In Mena Regionmentioning
confidence: 99%